Classroom assessment in multiple languages a handbook for teachers - Gottlieb, Margo (Thousand Oaks, CA Corwin, A Sage Publishing Company, 2021)
"Assessment is the bedrock of academic success in educational circles, but without assessment in multiple languages it is impossible to make valid inferences about multilingual student performance. "Assessing Learning in Multiple Languages" demonstrates the additive value of assessment in multiple languages by giving teachers tips for weaving such assessment strategies into their instruction. Using the assessment cycle as an organizing principle for the work, it portrays MLLs in a variety of contexts, provide evidence of MLLs' language development, and brings the personal dimension of socio-emotional development into sharp focus by aiming to build MLL agency and autonomy. This gives educators the ability to understand the rationale for and cite evidence of the value and benefits of assessment in multiple languages. It also provides tools teachers need to be more precise and effective in their assessments, and it will give MLLs a voice in the planning and enacting of their assessments. This is, in many ways, a cutting edge text as it gathers and synthesizes a growing body of research around the subject of multilingual programs, proficiency growth, and academic achievement"--
Includes bibliographical references (pages 209-219) and index.
Keywords: Educational tests and measurements; Multilingual education; Language and languages -- Ability testing; Electronic books